Smoking behaviour and preferences for cessation support among clients of an Indigenous community‐controlled health service. (2nd March 2018) - Cockburn, Nicole; Gartner, Coral; Ford, Pauline J.
Abstract: Introduction and Aims: Reducing smoking prevalence among Indigenous Australians is a vital part of closing the health gap between Indigenous and non‐Indigenous Australians. Community‐controlled health clinics are an important setting for delivering smoking cessation advice and assistance. This study measured tobacco and e‐cigarette use, knowledge of smoking‐related health effects, motivations to quit and interest in cessation aids. Design and Methods: Clients of Aboriginal & Torres Strait Islander Community Health Service dental clinics in Southeast Queensland ( n = 421) completed a brief written questionnaire while in the waiting room. Results: Nearly half ( n = 184, 47%) of the participants currently smoked daily, of which 9% ( n = 7) currently used e‐cigarettes. Few smokers (8%, n = 13) had no intention to quit smoking. For current smokers, previously used quit methods were abrupt cessation (42%, n = 78), nicotine replacement therapies (NRT; 25%, n = 45), prescription medications (23%, n = 43), e‐cigarettes (9%, n = 17) and other methods (3%, n = 6). Current smokers were most interested in cutting down (85%, n = 110), abrupt cessation (75%, n = 98) and free NRT (72%, n = 101). Fewer (34%, n = 36) were interested in purchasing NRT for smoking cessation. Discussion and Conclusions: Our study found there was interest in accessing smoking cessation aids among the clients of this community‐controlled health clinic, particularly if provided free of charge. Embedding smoking cessation advice and assistance into a range of community‐controlled health clinics could provide opportunities for addressing the high smoking prevalence among Indigenous Australians.